2021
DOI: 10.1038/s41419-021-04347-7
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of ubiquitin-like modifier-activating enzyme 2 promotes apoptosis of clear cell renal cell carcinoma cells

Abstract: Small ubiquitin-related modifier (SUMO) proteins are involved in the development of tumors. Ubiquitin-like modifier-activating enzyme 2 (UBA2) is an important member of the SUMO modification system; however, its role in clear cell renal cell carcinoma (ccRCC) is unclear. Therefore, we investigated the expression and function of UBA2 in ccRCC. Both mRNA and protein expression levels of UBA2 were found to be higher in ccRCC than in normal renal tissues and significantly related to the tumor size, Fuhrman grade, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Database analysis revealed that it was expressed in the cytoplasm predicted from UniProt 24 . UBA2-KD promotes the apoptosis of clear cell renal cell carcinoma cells 25 . Apoptosis-related phenotypes are discussed in this study, as apoptosis and autophagy are related to cancer 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Database analysis revealed that it was expressed in the cytoplasm predicted from UniProt 24 . UBA2-KD promotes the apoptosis of clear cell renal cell carcinoma cells 25 . Apoptosis-related phenotypes are discussed in this study, as apoptosis and autophagy are related to cancer 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Database analysis revealed that it was expressed in the cytoplasm predicted from UniProt [24]. UBA2-KD promotes the apoptosis of clear cell renal cell carcinoma cells [25].…”
Section: Tma7 Is Associated With Autophagy Of Lscc Cellsmentioning
confidence: 99%
“…In renal cell carcinoma, significantly increased UBA2 expression is related to higher stages and poorer prognosis. Downregulation of UBA2 promoted apoptosis and inhibited proliferation (Zhang et al 2021 ). In small cell lung cells, UBA2 expression is significantly upregulated; however, its knockdown suppresses the migration, invasion, and growth of lung cells and increases their sensitivity to chemotherapeutic drugs cisplatin and etoposide (Liu et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ubiquitin-conjugating enzyme E2T has been reported to play a critical role in ccRCC progression and may be a potential therapeutic target for ccRCC [ 17 ]. Recently, ubiquitin-like modifier-activating enzyme 2, an important member of the SUMO modification system, was found to promote the cell growth of ccRCC [ 18 ]. Considering the ambiguous relationship between ubiquitination and prognosis of ccRCC, developing a lncRNA signature-based model has an important clinical value in the prognosis of ccRCC.…”
Section: Introductionmentioning
confidence: 99%